Analyzing English Language Learning in Elementary Schools During the COVID-19 Pandemic: Challenges and Insights - Roni, Roni; Sunandar, Sunandar; Hermansyah, Sam; Nurbaya, St. (Majesty Journal, 2023)
The COVID-19 pandemic significantly transformed English language learning in elementary schools by shifting instruction from face-to-face classrooms to online and distance learning environments. This study aims to analyze the implementation, challenges, and pedagogical insights of English language learning in elementary schools during the COVID-19 pandemic. The study employed a qualitative literature review design by examining relevant national and international journal articles, books, and scholarly reports published up to 2023. The selected literature was analyzed through thematic content analysis by identifying recurring themes related to digital learning media, teacher roles, student participation, parental involvement, and learning barriers. The findings indicate that English learning during the pandemic was commonly implemented through digital platforms and media such as WhatsApp, Zoom, Google Meet, Microsoft Teams, YouTube, PowerPoint, pictures, videos, and audiovisual materials. These media supported vocabulary development, listening practice, pronunciation modeling, reading activities, and student engagement. However, the implementation of online English learning also faced several challenges, including limited internet access, unstable network connectivity, lack of digital devices, economic constraints, low student discipline, reduced interaction, limited teacher preparation, and difficulties in assessing students’ actual language performance. The study concludes that effective English learning for elementary students in emergency or technology-mediated contexts requires interactive, contextual, age-appropriate, and student-centered learning activities supported by teacher digital competence and parental involvement. The findings imply that schools should strengthen digital infrastructure, teacher training, and home-school collaboration to improve the quality and equity of English learning in elementary education.